2020
DOI: 10.1162/jocn_a_01508
|View full text |Cite
|
Sign up to set email alerts
|

Complexity Matching: Brain Signals Mirror Environment Information Patterns during Music Listening and Reward

Abstract: Understanding how the human brain integrates information from the environment with intrinsic brain signals to produce individual perspectives is an essential element of understanding the human mind. Brain signal complexity, measured with multiscale entropy, has been employed as a measure of information processing in the brain, and we propose that it can also be used to measure the information available from a stimulus. We can directly assess the correspondence between brain signal complexity and stimulus compl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
0
13
1
Order By: Relevance
“…To do this, we evaluated the Pearson correlation coefficient between the LZ changes measured in the various ROIs across subjects. It was observed that the correlation between ROIs is substantially increased when subjects perceive an external stimulus (either music or video; see Supplementary Material), which could be indicative of a form of “complexity matching” (26) in which neural dynamics are entrained by the external stimulus, obscuring the relationship between neurodynamics and subjective experience. This observation was also verified via multivariate regression modelling, this time using ROI-ROI correlation values as target.…”
Section: Resultsmentioning
confidence: 99%
“…To do this, we evaluated the Pearson correlation coefficient between the LZ changes measured in the various ROIs across subjects. It was observed that the correlation between ROIs is substantially increased when subjects perceive an external stimulus (either music or video; see Supplementary Material), which could be indicative of a form of “complexity matching” (26) in which neural dynamics are entrained by the external stimulus, obscuring the relationship between neurodynamics and subjective experience. This observation was also verified via multivariate regression modelling, this time using ROI-ROI correlation values as target.…”
Section: Resultsmentioning
confidence: 99%
“…We regard statistical control as necessary to establish entropy effects that are not capturable by traditional linear indices (such as PSD characteristics). While some studies have shown joint effects of interest in MSE and (band-limited) spectral power [15,16,18,19,[111][112][113][114][115][116][117], others identified unique MSE effects [22,[118][119][120]. However, the (mis)match between time-scales and frequencies may not always be readily apparent, at least in part due to the various issues raised here.…”
Section: Recommendations For Future Applicationsmentioning
confidence: 87%
“…Created with BioRender.com. electroencephalography (M/EEG) [142] provides a second point of contact, with abnormalities in dynamic complexity suggested as indicative of mental illness [143], while music engagement has been suggested to reflect and perhaps affect dynamic complexity [144,145].…”
Section: Music and Brain Network Dynamicsmentioning
confidence: 99%